2019
DOI: 10.1016/j.adolescence.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and identity diffusion among inpatient adolescents: The role of reflective function

Abstract: Introduction: Identity integration, as opposed to identity diffusion, has been associated with greater self-esteem, meaning in life, and functioning. Trauma may have negative effects on identity; however, few studies have examined trauma and identity among adolescents, particularly those with psychiatric disorders. Moreover, factors that may promote healthy identity in adolescents who have experienced trauma have not been identified. This study aimed to test associations between childhood maltreatment and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 68 publications
4
38
1
2
Order By: Relevance
“…One possibility is that clinical heterogeneity within SAD may relate to differences across the life span in exposure to traumatic events, such as childhood maltreatment. Prior work has demonstrated that childhood maltreatment is associated with anxiety and depression (Iffland et al, 2012;Simon et al, 2009;Vachon et al, 2015), later identity diffusion (i.e., when a person's identity remains unresolved and not fully formed), altered self-perception (Scott et al, 2014), and negative self-referential processing (Penner et al, 2019;Toth et al, 2000). Given the known relationships between childhood maltreatment, psychopathology, and altered self-referential processing, we hypothesized that heterogeneity in SAD, in the form of more extreme negative self-beliefs and altered DMN activation, might be associated with greater exposure to childhood maltreatment.…”
Section: Empirical Articlementioning
confidence: 99%
“…One possibility is that clinical heterogeneity within SAD may relate to differences across the life span in exposure to traumatic events, such as childhood maltreatment. Prior work has demonstrated that childhood maltreatment is associated with anxiety and depression (Iffland et al, 2012;Simon et al, 2009;Vachon et al, 2015), later identity diffusion (i.e., when a person's identity remains unresolved and not fully formed), altered self-perception (Scott et al, 2014), and negative self-referential processing (Penner et al, 2019;Toth et al, 2000). Given the known relationships between childhood maltreatment, psychopathology, and altered self-referential processing, we hypothesized that heterogeneity in SAD, in the form of more extreme negative self-beliefs and altered DMN activation, might be associated with greater exposure to childhood maltreatment.…”
Section: Empirical Articlementioning
confidence: 99%
“…1.3 | CEA, uncertain reflective functioning, and problematic use of SNS CEA has a negative impact on the development of reflective functioning (Penner et al, 2019). Reflective functioning is the manifestation of the ability to mentalize (Fonagy et al, 2002), which refers to one's capacity for understanding the mental states (i.e., thoughts, feelings, wishes, and desires) underlying human behavior.…”
mentioning
confidence: 99%
“…Items are rated on a 5-point Likert scale (range: 1 "Never True, " to 5 "Very Often True"). Psychometric properties have been established for the CTQ-SF (49), and the CTQ-SF has been used with adolescent inpatients specifically [e.g., (50)]. Cronbach's alpha were as follows for CTQ-SF subscales in the current study: emotional abuse (α = 0.86), sexual abuse (α = 0.96), physical abuse (α = 0.63), emotional neglect (α = 0.90), and physical neglect (α = 0.54).…”
Section: Trauma Historymentioning
confidence: 99%